Impact factors and mechanisms of iron-modified corn stover biochars activating urea-hydrogen peroxide to remove rhodamine B in water - Ke Yang; Baowei Zhao; Qi Guo; Xin Zhang; Jianglong Pan (Desalination and Water Treatment)
Advanced oxidation technology based on urea-hydrogen peroxide (UHP) has attracted much attention for its excellent performance in degrading dyes (e.g. Rhodamine B, RhB) in water. Aiming at the current situation that the activation of UHP by modified catalysts requires much cost and complicated raw materials, together with few systematical comparisons and unclear acitivation and degradation mechanisms, the iron-modified corn stover biochars (Fe-CSB300, Fe-CSB500 and Fe-CSB700) were prepared using corn stover as raw material and ferrous sulphate as modifier through impregnation and pyrolysis (300°C, 500°C and 700°C). The Fe-CSB catalysts were characterized, and the effects of Fe-CSB activation to UHP for the oxidative removal of RhB from water were compared. The results showed that RhB removal was nearly 100 % with Fe-CSB300 and Fe-CSB700 as catalysts, while 77.13 % with Fe-CSB500 as catalyst under the conditions of RhB 40 mg/L, pH= 5, Fe-CSB 100 mg/L, and UHP 100 mg/L. Three cycle experiments have demonstrated that Fe-CSB exhibits excellent stability and reusability during the recycling process. Co-existing anions inhibited the degradation. Active species for RhB removal were mainly·OH and 1O2, and the main degradation pathways were bond cleavage, carboxylation and hydroxylation. These results could provide a scientific basis for applying UHP advanced oxidation technology to remove dyes from water.